49.5k views
0 votes
Solve the following equation algebraically. Show your work.

6=x+23

2 Answers

4 votes

Answer: 23+x=6

-23 -23

1x/1 -17/1

x=-17

Explanation:

User Chris Lacy
by
5.8k points
2 votes

Answer:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

-6*x-(23)=0

Step by step explanation :

Pulling out like terms

Pull out like factors :

-6x - 23 = -1 • (6x + 23)

Solving a Single Variable Equation:

2.1 Solve : -6x-23 = 0

Add 23 to both sides of the equation :

-6x = 23

Multiply both sides of the equation by (-1) : 6x = -23

Divide both sides of the equation by 6:

x = -23/6 = -3.833

Therfor the answer is : x = -23/6 = -3.833

User HumbleBee
by
5.8k points